Moral suasion in regional government bond markets - Jana Ohls (Deutsche Bundesbank, 2017)
In the context of the German regional government bond market, this paper studies the hypothesis that governments use moral suasion to persuade home government-owned banks to hold more home government debt. The empirical approach makes use of German banks' ownership structure, heterogeneity in the states' fiscal strength and detailed bank-level panel data on German banks' state bond portfolio on the security- and bank-level for the time period Q4:2005-Q2:2014. Results show that home state-owned banks hold a significantly higher amount of home state bonds than other home banks when fiscal fundamentals of the home state are weak. Banks located in other German states hold fewer state bonds in these situations. These findings are in line with moral suasion by state governments and are robust against controlling for observed and unobserved alternative incentives for banks' (home) state bond holdings such as risk-shifting by banks, lending opportunities or information asymmetries.
Keywords: G11; G18; G21; G28; 330; banks' sovereign bond portfolios; home bias; moral suasion; political economy of banking